Pengaruh Moderasi Beragama Terhadap Prilaku Keagamaan Generasi Z: (Studi Kasus Di SMP Negeri 04 Kualuh Hulu Labuhanbatu Utara) - Wibowo, Muhammad Agung; Harahap, Indra; Siregar, Husna Sari (Jayapangus Press, 2024)
The role of religious moderation is very important in the school environment, because school is the place where students spend most of their time and receive a lot of influence from peers and teachers. In a multicultural environment such as at SMP Negeri 04 Kualuh Hulu, religious moderation can help students develop mutual respect and understanding of existing differences. This research aims to explore the influence of religious moderation on the religious behavior of generation Z at SMP Negeri 04 Kualuh Hulu. The research method used is field research with a descriptive qualitative approach. The analysis technique applied is Descriptive Analysis which provides a complete and orderly picture of the research object. Data was collected through observation and interviews with primary data sources in the form of three teachers and three students, as well as secondary data from previous studies. The research results show that students' understanding of religious moderation at SMP Negeri 04 Kualuh Hulu is quite diverse. Some students understand and apply the concept of religious moderation well, while others still show extreme or apathetic tendencies. The implementation of religious moderation in this school helps some students develop attitudes of tolerance and mutual respect, but there are still challenges in implementing it as a whole. Family environmental factors and the influence of social media also influence students' understanding and behavior regarding religious moderation. Therefore, further efforts and collaboration between schools and parents are needed to increase understanding and implementation of religious moderation among students.